RELATIONSHIPS BETWEEN FACTORS AFFECTING THE TRANSFER OF VOCATIONAL SAFETY TRAINING IN THE WORKPLACE: THE CASE STUDY OF ALUMINIUM OF GREECE - Brinia, Maria Vasiliki; Efstathiou, Maria (Journal of Technical Education and Training, 2013)
The purpose of this research is to present the process of the transfer of safety training in the company “Aluminium of Greece”. Furthermore, it presents initial attempts to identify key factors affecting transfer of training and the correlation between these factors. The survey conducted among 88 employees using questionnaires. The findings show that employees place great importance on safety training. Motivation for learning and transfer, the opportunity for implementation and personal ambition were associated in our study with some and / or all factors examined (age, experience, level of education, etc.). Additionally, the researchers identified the need for evaluation of education not only immediately after its end, but overall evaluation especially some time after the training, in order to examine the value of education as an investment.